2017
DOI: 10.1021/acsami.7b01585
|View full text |Cite
|
Sign up to set email alerts
|

Self-Cleaning Membranes from Comb-Shaped Copolymers with Photoresponsive Side Groups

Abstract: In this study, we present a novel self-cleaning, photoresponsive membrane that is capable of removing predeposited foulant layers upon changes in surface morphology in response to UV or visible light irradiation while maintaining stable pore size and water permeance. These membranes were prepared by creating thin film composite (TFC) membranes by coating a porous support membrane with a thin layer of novel comb-shaped graft copolymers at two side-chain lengths featuring polyacrylonitrile (PAN) backbones and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…Recently some new self-cleaning systems have been proposed utilizing the photocatalytic effect for the degradation of organic pollutants adsorbed on a surface (Yusof et al 2018). Moreover some "smart" surfaces have been also developed and the self-cleaning effect can be UV (Kaner et al 2017;Pifferi et al 2015) or laser-induced (Zheng et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently some new self-cleaning systems have been proposed utilizing the photocatalytic effect for the degradation of organic pollutants adsorbed on a surface (Yusof et al 2018). Moreover some "smart" surfaces have been also developed and the self-cleaning effect can be UV (Kaner et al 2017;Pifferi et al 2015) or laser-induced (Zheng et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the switchability of SP‐based materials, which become zwitterionic and thus more hydrophilic under UV light, can be used to generate antifouling surfaces …”
Section: Membrane Processesmentioning
confidence: 99%
“…Recently, Kaner et al prepared thin film membranes with antifouling properties due to light induced changes in surface morphology at constant pore size and water permeability. The self‐cleaning membranes were obtained by coating a porous PVDF membrane with a thin layer of comb‐shaped graft copolymers at two side‐chain lengths featuring polyacrylonitrile backbones and photoreactive SP methacrylate side chains.…”
Section: Membrane Processesmentioning
confidence: 99%
“…Furthermore, there is a significantly lower water flux decline of the zwitterionic polyamide membrane compared to the pristine polyamide membrane in filtrating a mixed feed solution containing organic foulants, such as bovine-serum albumin, alginate, and natural organic matter. Kaner et al [60] reported a novel self-cleaning, photo-responsive membrane, and found that the pre-deposited foulant could be removed from the membrane surface in response to UV or visible light irradiation while maintaining stable pore size and water permeance. This is because the hydrophobic spiropyran groups within the membrane are converted to hydrophilic zwitterionic merocyanine groups by irradiation with UV light, resulting in the release of adsorbed molecules and the full recovery of the initial water flux.…”
Section: Influence Of “Ion Pairs” Characteristic Of Nanofiltrationmentioning
confidence: 99%